Analisis Strategi Pemasaran Mie Sedaap Dalam Meningkatkan Minat Beli Konsumen - Malihah, Lola; Wushulinsana, Wushulinsana; Zaitun, Zaitun (JURNAL ADMINISTRASI KANTOR; Vol 11 No 1 (2023): Jurnal Administrasi Kantor (Juni 2023), 2023)
This study aims to determine the strategies used by Mie Sedaap to increase consumer buying interest. Mie Sedaap is a noodle brand from a national company PT. Wing Surya (Wings Food), Mie Sedaap is the second largest market leader in instant noodles after its competitor, Indomie. Therefore, as a competitor PT. Wingsfood must be able to innovate with an effective and planned marketing strategy to increase consumer buying interest which results in a decision to buy Mie Sedaap products. This research is a literature study by examining related theories as reference material. Based on the analysis that has beendone it can be known that mie sedap always innovates its products by releasing new flavor variants as one of its strategies to increase consumer buying interest in its products. In addition, mie sedaap also takes advantage of advertising media, and also cooperate with the publicfigure to promote its products, this also aims to be able to boost customer buying interest and also as a form of promotion to new potential customers .   Keywords : Mie Sedaap, buying interest, mix marketing.